Double trouble - Dale, Jenny; Reid, Mick; Rowe, Michael (London : Macmillan, 1997)
Neil is responsible for taking care of Sugar and Spice, two very spoiled dogs who disappear from their kennel.
5.2
3-6
Keywords: Dogs -- Fiction